Does the Consumer Benefit from Price Instability? - Howell, L. D. (Quarterly Journal of Economics, 1945)
Journal Article Does the Consumer Benefit from Price Instability? Get access L. D. Howell L. D. Howell Bureau of Agricultural Economics, Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 59, Issue 2, February 1945, Pages 287–295, https://doi.org/10.2307/1884829 Published: 01 February 1945